Lean ammonia-fueled engine operation enabled by hydrogen-assisted turbulent jet ignition - Reggeti, Shawn A.; Northrop, William F. (Frontiers in Mechanical Engineering, 2024)
Anhydrous ammonia (NH3) use in internal combustion engines represents a zero-carbon energy solution that is fully sustainable if NH3 is generated renewably. An active hydrogen-fueled pre-chamber to induce turbulent jet ignition is investigated in this work as a means to enhance ignition energy and turbulent flame speed in an NH3 fueled engine. The strength of the turbulent jets, and thus their effectiveness in igniting the main-chamber and enhancing combustion, is highly dependent on pre-chamber equivalence ratio and hydrogen fraction. Local pre-chamber mixtures are varied in the present study by investigating a range of pre-mixed intake NH3-air equivalence ratios (ϕ = 0.5–1) under a consistent hydrogen direct injection strategy in the pre-chamber. Additionally, given the knock-resistance of NH3, multiple compression ratios were studied to investigate the impact on efficiency, emissions, and the combustion process. Results show a clear trade-off where leaner intake equivalence ratios enhance the reactivity of the pre-chamber (greater local hydrogen fraction and closer to stoichiometry) but reduce the reactivity of the main-chamber (lean and slow flame speed). Spark timing optimizes the trade-off under a fixed injection strategy; advancing spark provides more time for combustion to occur in the main-chamber but inhibits pre-chamber reactivity for a less energetic ignition of the main chamber. Optimal indicated thermal efficiency and minimum unburned NH3 and N2O emissions occur around 0.7–0.8 equivalence ratio for all compression ratios. Conversely, NOx is highest at these equivalence ratios but could theoretically be eliminated using selective catalytic reduction aftertreatment using the NH3 present in the exhaust.